The Commercial Job in Abu Tayara Street in the Municipality of Al- Dora (Journal of the College of Education for Women, 2020)
The commercial job is one of the most important businesses in the cities as there is no city can exist without commercial markets to offer service to its inhabitants. This study aims to distribute the commercial function in Abu Tayara Street located in the municipality of Al-Dora by highlighting the size of such businesses in this street. It focuses on analyzing the change that has occurred due to the usages of the commercial land not only in the residential areas, but also in various aspects associated with the growth of the population in the city. Both expansion and development of the economic and social aspects in the area have increased the demand for commercial services. So, the research focuses on the aspects of functional specialization in Abu Tayara Street and the role of social activities in meeting the needs of the residents in the area and the surrounding neighborhoods. The research concludes that the geographical factors have significantly increased the growth and development of the commercial function in Abu Tayara Street. Change and diversity within this street have offered all commercial commodities and services, and have created multiple job opportunities for its residents as well as the nearby areas........